Qur'anic legal literacy on the principle of shul (Islah) in family dispute resolution - Aprinelita, Aprinelita; Hidayatullah, Hidayatullah (Priviet Social Sciences Journal, 2026)
Family disputes arise when there is a conflict or incompatibility between parties. In this sense, a problem can be interpreted as a situation in which the parties experience pros and cons or incompatibility with the agreement made between them. This is still related to the status of humans as social beings. The existence of disputes between humans inspires the birth of the desire to resolve the conflict/dispute that occurs between them. In dispute resolution, Islam places great emphasis on peace to anyone who is in conflict, and the settlement of disputes arises more from the wishes and initiatives of the parties to the dispute, so that mediators play a petrified role in reaching agreements. In Islamic law, the mediation procedure used to resolve family disputes is called al-sulh, which means to settle, involving a hakam. The processes and facts of society are different. The mediation stage is not necessary if the couple can resolve conflicts within their families. In such situations, they can only resolve the issue with the agreement they made before, and there is no further process. However, when conflicts cannot be resolved simultaneously, families require a trusted family mediator or judge. Therefore, certain stages in this mediation process are necessary to reach an agreement between the two parties. First, each party to the conflict must be willing to present its grievances to the mediator. The second process is peace carried out by third parties. A third party does this by identifying the root cause of the conflict. The third process begins when the midpoint is determined. This process requires the approval of each family that has problems with the solution offered by a mediator. The fourth or an advanced process can be initiated. The mediator in the community is usually a religious figure or community leader, such as a kyai, a hamlet head, or maybe even a hakam, or a trusted family member.